Metabolic diversity and ecological niches of Achromatium populations revealed with single-cell genomic sequencing - Mansor, Muammar; Hamilton, Trinity L.; Fantle, Matthew S.; Macalady, Jennifer (Frontiers in Microbiology, 2015)
Large, sulfur-cycling, calcite-precipitating bacteria in the genus Achromatium represent a significant proportion of bacterial communities near sediment-water interfaces throughout the world. Our understanding of their potentially crucial roles in calcium, carbon, sulfur, nitrogen, and iron cycling is limited because they have not been cultured or sequenced using environmental genomics approaches to date. We utilized single-cell genomic sequencing to obtain one incomplete and two nearly complete draft genomes for Achromatium collected at Warm Mineral Springs, FL. Based on 16S rRNA gene sequences, the three cells represent distinct and relatively distant Achromatium populations (91-92% identity). The draft genomes encode key genes involved in sulfur and hydrogen oxidation; oxygen, nitrogen and polysulfide respiration; carbon and nitrogen fixation; organic carbon assimilation and storage; chemotaxis; twitching motility; antibiotic resistance; and membrane transport. Known genes for iron and manganese energy metabolism were not detected. The presence of pyrophosphatase and vacuolar (V)-type ATPases, which are generally rare in bacterial genomes, suggests a role for these enzymes in calcium transport, proton pumping, and/or energy generation in the membranes of calcite-containing inclusions.